China : Agenda for Water Sector Strategy for North China, Volume 3. Statistical Annexes - World Bank (Washington, DC, 2013)
The acute water shortage, and pollution problems in North China have been exacerbated by the continued population growth, and the accelerated industrial expansion over the past half-century, conducive to increasingly severe freshwater shortages, and catastrophic consequences for the future. Significant commitments need to be made to rapidly implement strategies to bring water resource utilization back into a sustainable balance. The report reviews past and present situations, focusing on the future impacts of various social, and economic growth scenarios within the context of water management, where preconditions for its success are the combined requirements of complementary pricing, management, and regulatory reforms in water resources (including groundwater, water pollution, and wastewater reuse). Findings suggest a water demand management as proposed in the action plan - with further water price increases, and improving irrigation efficiency. Agricultural productivity depends on irrigation efficiency, thus water management calls for water-savings measures, low-yield land improvement, and, large-scale systems rehabilitation. Structural water pollution remedy measures, should focus on industrial wastewater pretreatment, and internal reuse of processed water, pollution prevention programs, and combined industrial, and municipal treatment plants, to include as well artificial groundwater recharge (wastewaters and floodwaters). Institutional aspects will require further strengthening, regarding water resource allocation, protection, and financing.